Aspek-aspek Keuangan Yang Mempengaruhi Perilaku keuangan (Studi Kasus Pada Mahasiswa Pengguna Paylater Universitas Wira Bhakti): (Studi Kasus Pada Mahasiswa Pengguna Paylater Universitas Wira Bhakti) - Miftahul Jannah; Sitti Murniati; Sumarni S (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
ABSTRACT This study aims to: (1) determine whether financial literacy influences financial behavior; (2) determine whether lifestyle influences financial behavior; (3) determine whether financial technology influences financial behavior; and (4) examine whether financial literacy, lifestyle, and financial technology simultaneously influence financial behavior. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to active students of Universitas Wira Bhakti Makassar who use the Spaylater service. The sample consisted of 81 respondents. The variables studied include financial literacy, lifestyle, and financial technology. The data were analyzed using descriptive analysis, classical assumption tests, multiple linear regression, partial test (t-test), simultaneous test (F-test), and the coefficient of determination (R²) to assess the effect of each variable on students’ financial behavior. The results show that financial literacy has no positive or significant effect on financial behavior in using Spaylater. Lifestyle has a positive and significant effect, while financial technology has a positive but not significant effect on financial behavior. These findings suggest that even though students have access to financial information and technology, lifestyle is the dominant factor influencing financial behavior in the use of Spaylater. Therefore, financial behavior development efforts should consider students’ consumption patterns and lifestyle, not just improving literacy or access to financial technology. Keywords: Financial Behavior; Spaylater; Financial Literacy; Lifestyle; Financial Technology